Full Day School Policy Analysis at The Islamic Education Unit - Nuzula, Jannatul Firdausi; Latif, Muhammad Sabri; Aziz, Abdul; Suti’ah (CENDEKIA, 2024)
This research aims to find out the government's policy on a full-day school in shaping the character of students in Islamic Education institutions, namely how the history of the full-day school policy is determined, how the implementation of the full-day school policy and how the implications of the creation of the full day school policy. This research is a type of library research that is centered on the study of some literature related to the issues discussed such as Permendikbud No. 23 of 2017, the results of research on Full Day School and the regulation. The result of this study is that the full-day school policy has been implemented simultaneously in 2017. The Minister of Education and Culture launched the full-day school policy through the authority of Permendikbud No. 23 of 2017 concerning school days, then followed by Presidential Regulation No. 87 of 2017 concerning character education. The implementation of the full-day school policy in shaping the character of students requires structured management, such as good planning, curriculum innovation, excellent programs, and extracurricular activities. The positive implications of the full-day school policy can shape the character of students, but it cannot be denied that there are negative implications that cause a lack of student interaction with family and society, causing boredom if learning is not innovative and interactive. The negative impact of the full-day school policy also has an impact on teacher work discipline. Therefore, the implementation of full-day schools needs regular evaluation to produce quality education and generation.